2008
DOI: 10.1002/ca.20695
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic innervation of the developing heart: Origins and function

Abstract: Maintenance of homeostatic circulation in mammals and birds is reliant upon autonomic innervation of the heart. Neural branches of mixed cellular origin and function innervate the heart at the arterial and venous poles as it matures, eventually coupling autonomic output to the cardiac components, including the conduction system. The development of neural identity is controlled by specific networks of genes and growth factors, whereas functional properties are governed by the use of different neurotransmitters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 83 publications
1
44
0
1
Order By: Relevance
“…The parasympathetic vagal cardiac system and its cardiac branches are consistent among primates. Interestingly, the comparative anatomical findings of the variable sympathetic and constant parasympathetic ECNSs in primates are similar to the mammalian ontogeny of cardiac innervation; however, the sympathetic cardiac innervation has been shown to occur at later stages than the parasympathetic vagal cardiac innervation (Kirby et al, 1980;Shoba and Tay, 2000;Hildreth et al, 2009).…”
Section: Comparative Anatomy Of Ecns In Strepsirrhines With Evolutionmentioning
confidence: 75%
See 1 more Smart Citation
“…The parasympathetic vagal cardiac system and its cardiac branches are consistent among primates. Interestingly, the comparative anatomical findings of the variable sympathetic and constant parasympathetic ECNSs in primates are similar to the mammalian ontogeny of cardiac innervation; however, the sympathetic cardiac innervation has been shown to occur at later stages than the parasympathetic vagal cardiac innervation (Kirby et al, 1980;Shoba and Tay, 2000;Hildreth et al, 2009).…”
Section: Comparative Anatomy Of Ecns In Strepsirrhines With Evolutionmentioning
confidence: 75%
“…Experimental and developmental studies of the autonomic cardiac nervous system have also been conducted in animals such as the mouse, rat, rabbit, chick, and dog (Armour et al, 1972;Benítez et al, 1959;Brack et al, 2011;Gomez, 1958;Haws and Burgess, 1978;Hildreth et al, 2008Hildreth et al, , 2009Kirby et al, 1980;Kuratani et al, 1991;Kuratani and Tanaka, 1990;Levy et al, 1966;Mabe and Hoover, 2011;Meyer et al, 2010;Mizeres, 1955Mizeres, , 1957Mizeres, , 1958Mizuno et al, 2010;Oliveira et al, 2010;Roberts, 1991;Schwartz, 2010;Scherlag et al, 2011;Shaner, 1930;Shoba and Tay, 2000;Uchida et al, 2010;Verberne et al, 1998). However, huge differences in the cardiac nervous system between humans and the experimental animals have been recognized (Batulevicius et al, 2003;Brugnaro et al, 2003;Kawashima, 2011;McKibben and Getty, 1968;Rysevaite et al, 2011;Pauza et al, 2002a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian and avian ontogenetic developmental studies of the ACNS are detailed in a number of papers (Kirby et al, 1980;Kuratani and Tanaka, 1990;Verberne et al, 1998;Shoba and Tay, 2000;Hildreth et al, 2008Hildreth et al, , 2009). In the chick, the innervation of the outflow tract (arterial porta) by the parasympathetic cardiac branches occurred between stages 28 and 29 of Humburger and Hamilton (HH), whereas the positive HNK1 staining is first observed at the 24th stage and reaches the venous sinus by the 26th stage, and further vagal cardiac branches develop (Kuratani and Tanaka, 1990;Verberne et al, 1998;Hildreth et al, 2009).…”
Section: Phylogeny In Vertebrates and Mammalian Ontogeny Of The Acnsmentioning
confidence: 99%
“…In the chick, the innervation of the outflow tract (arterial porta) by the parasympathetic cardiac branches occurred between stages 28 and 29 of Humburger and Hamilton (HH), whereas the positive HNK1 staining is first observed at the 24th stage and reaches the venous sinus by the 26th stage, and further vagal cardiac branches develop (Kuratani and Tanaka, 1990;Verberne et al, 1998;Hildreth et al, 2009). In the mouse, the parasympathetic vagal nerves are first seen in the venous porta at E10.5 (10.5 days after fertilization, equivalent to HH20 in the chick) and reach the heart by E12.5 (HH24), whereas the innervation of the outflow (arterial porta) occurs slightly later than seen in the chick (Hildreth et al, 2008).…”
Section: Phylogeny In Vertebrates and Mammalian Ontogeny Of The Acnsmentioning
confidence: 99%
“…Sympathetic neurons have their cell bodies primarily in the paravertebral stellate ganglion, whereas parasympathetic cell bodies are located in the cardiac ganglia [5]. The cells contributing to the cANS are derivatives of neural crest cells (NCCs) and cells of the nodose placode [6,7]. Kroese et al demonstrated that prior to cardiac sympathetic innervation of the developing chicken embryo, the heart already responds to the catecholamine epinephrine [8].…”
Section: Introductionmentioning
confidence: 99%